Sameness in diversity food and globalization in modern America - Jayasanker, Laresh, 1972-2018 (California studies in food and culture, 2020)
"Americans of the 1960s, accustomed to frozen dinners and soupy casseroles, would have trouble navigating the grocery aisles and restaurant menus of today. There, they would find once-exotic ingredients-like mangoes, hot sauces, kale, kimchi, and coconut milk-that have become standard in contemporary Americans' diets. Laresh Jayasanker explains how food choices have expanded, even as food companies have consolidated. These changes reflect other transformations in transportation, suburbanization, immigration, and global production. Drawing on menus, cookbooks, trade publications, interviews, and company records, Jayasanker explores Americans' changing eating habits to illuminate the impacts of globalization and immigration on American culture"--